Impact of Islamicity on the productivity of conventional and islamic banks in selected Southeast Asian countries - Mamat, Hasrul Nizam; Kamarudin, Fakarudin; Ali, Mohsin; Hussain, Hafezali Iqbal (Elsevier B.V., 2024)
This study provides a new understanding of how bank-specific characteristics, the macroeconomic environment, and Islamicity affect the productivity of conventional banks (CBs) and Islamic banks (IBs) in selected Southeast Asian countries. The data of 153 banks, collected between 2015 and 2020, were used, and the influence of the selected factors was investigated by using panel data approaches, as well as the data envelopment analysis-based Malmquist productivity index (DEA-MPI). In the first-stage analysis, bank productivity was measured by using total factor productivity changes (TFPC), and in the second-stage analysis, panel regression analysis was performed, specifically, multiple panel regression analysis, which employed pooled ordinary least squares, a fixed-effects model, and a random-effects model. Parametric and nonparametric (Mann–Whitney and Kruskall–Wallis) tests found that the IBs were more progressive than the CBs. The findings indicated that unlike the IBs, change in the productivity of the CBs was adversely affected by economic Islamicity, as well as legal and governance Islamicity, which indicated that macroeconomic and legal structures that leaned toward Islamic values adversely affected the CBs. Meanwhile, the IBs were likely to be structured in line with such values and thus can mitigate the adverse impact of various factors. Both groups were negatively affected by human and political rights Islamicity, which indicated the use of a setup that could not benefit from Islamic values. This finding lends credence to the arguments in the literature that IBs mirror CBs in practice to remain competitive in their pricing based on market principles. The IBs were found to benefit from international relations Islamicity, which bodes well for the competitiveness of new players against the ancient setup of CBs in the globalized world.